تعاطي الحشيش في الفقه الإسلامي: دراسة مقارنة في ضوء النصوص الشرعية والفتاوى المعاصرة = Cannabis use in Islamic jurisprudence (fiqh): a comparative study in light of scriptural texts and fatāwā - Saising, Hanif; Artalim Zaim, Muntaha; Md. Sawari, Mohd. Fuad (International Islamic University Malaysia, 2025)
Abstract The issue of cannabis use constitutes a burgeoning legal challenge, presenting a significant dilemma for contemporary Islamic jurisprudence and the legal sphere. This is particularly true given the alarming escalation in drug proliferation and the resultant multifaceted negative impacts on individuals and society. While Islamic Fiqh has long established definitive rulings for traditional intoxicants like wine, the emergence of modern drugs in their various forms necessitates a specialized study. Such a study must move beyond mere apparent analogical reasoning to strike a balance between the enduring constants of the Sharīʿah and the evolving realities of the modern world. This research aims to offer an in-depth comparative jurisprudential study on the ruling concerning cannabis. It is grounded in monitoring and analyzing the established juristic opinions from the Islamic eras where cannabis was prevalent, while simultaneously integrating both classical and contemporary scholarly interpretations. Furthermore, the study seeks to critically analyze the Fatawa issued by contemporary Fiqh Academies and legal councils regarding its consumption, cultivation, distribution, and the specific matter of its therapeutic use. The study employs an analytical methodology for examining the sacred texts and the jurists' views, complemented by a comparative balancing approach between these sources and the modern Fatāwā. The anticipated conclusion is to articulate the precise Sharia-compliant controls and the overarching universal maxims governing this issue, thereby contributing to the formulation of a comprehensive and rigorous legal vision that is capable of addressing contemporary intellectual and social challenges.